Saberes etnomatemáticos na formação de professores indígenas do curso de licenciatura intercultural na Amazônia - Santos, Jonatha Daniel dos (2015)
This study aims to analyze how the practices and etnomatemáticos knowledge expressed by the Indians of the Amazon are thought in the training of indigenous teachers. The theoretical framework underlying this research consisted of two pillars: power relations, knowledge and governmentality, based on studies of Foucault (2008, 1979, 2005, 2011), Fischer (2012), Veiga-Neto (2011), Larrosa ( 2011), among others; Ethnomatematics, based on D'Ambrosio (2002, 2009, 2010, 2012), Knijnik (1996, 2006, 2012) and Paul Gerdes (1991, 2002, 2010). The subjects of academic research in Intercultural Basic Education Bachelor's Degree opting for axis Natural Sciences and Mathematics Intercultural. These individuals represent the ethnic groups: Surui-Paiter, Hawk Ikolen, Oro Win, Cinta Larga and Oro Waje. Currently all are teachers of their communities in the early years and the end of elementary school. However, just who complete the course will work on training who have chosen. To compose the empirical material were carried out narrative interviews during the month of February and March 2014. On such narratives carried out a genealogical discourse analysis covering aspects such as: the Amazon indigenous practices are addressed in teacher training / indigenous participants this research; the concepts of Ethnomatematics that are present in the formation process of these / the teachers / as; the implications of Ethnomatematics for your school practices. The interviews show that the etnomatemáticos knowledge of indigenous peoples of Rondônia participants of this thesis, are constituted as of governance mechanism and contraconduta in teacher education of indigenous teachers students with regard to mathematical knowledge of these people and their discussion with students in the school indigenous. However, reports indicate that the Ethnomatematics has been working in this space as a contraconduta strategy, since the teachers / students are indigenous (and has constituted) in the State, another way to lead and drive the other ( students of Indian schools) through their teaching practices. Such practices are in accordance with their training in Intercultural Bachelor of that during the course deepen the academic discussion on indigenous knowledge and its functionality in school, reframing their knowledge among younger people falling into the classrooms and it appropriated to meet such knowledge through the teaching practice of the indigenous teacher.